Potential inoculants of diazotrophic bacteria in Hibiscus sabdariffa L. (Research, Society and Development, 2023)
Hibiscus sabdariffa L., known as vinegar plant or sorrel is a vegetable classified as a Non-Conventional Food Plant (PANC), demanding high nitrogen fertility. The use of microorganisms to supply the nutrient demand is a viable alternative. Thus, the objective of this experimental research was to evaluate isolates of diazotrophic bacteria in the vegetative growth of hibiscus. The statistical design used was a randomized block design, with 8 treatments and 5 replications, totaling 40 experimental plots, each plot being a pot containing two plants. The treatments consisted of 6 different bacterial mix (B1, B2, B3, B4, B5 and B6) of strains kept in controlled storage in the Agricultural Microbiology Laboratory-UNIFENAS, plus 2 controls, positive control (PC), without inoculation, plus complete fertilization, negative control (NC), without inoculation and fertilization. The aerial part and roots were harvested 90 days after planting, evaluating the main biometric measurements. The treatment B4 using the strains HNFB3B and HJR3, presented the best result in the biometric variables of height, number of leaves and root biomass of the plant.